Análise das respostas ventilatórias, metabólicas e do controle autonômico cardiovascular durante testes de resistência muscular inspiratória e de determinação da pressão inspiratória crítica - Minatel, Vinicius (2017)
Respiratory muscle weakness has a strong relationship with autonomic cardiovascular control dysfunction and exercise limitation. For this reason, inspiratory muscle training programs (IMT) have been applied to improve respiratory muscle strength/endurance, exercise performance and autonomic cardiovascular control. However, the optimal IMT intensity to induce a better systemic response has not been defined yet. Therefore, we developed our First Study, that aimed to identify the inspiratory critical pressure (PThC) using the critical power model in healthy men, evaluate the ventilatory and metabolic responses at the PThC and identify the predictors variables of PThC and propose an equation to obtain it. The participants of the study (n=79) underwent the PThC protocol, which consisted of a progressive inspiratory threshold-loading test to set the sustained maximal inspiratory load (PThMAX). In a subsequent visit was carried out a constant load inspiratory exercise protocol (95%, 100% and 105%PThMAX). Both tests were performed until task failure using a linear inspiratory load resistor connected in series to a gas exchange analysis system. The inspiratory endurance time for each load was used to calculate the PThC, and the resulting value was tested using a constant load protocol performed in a different day from previous tests. Results showed that PThC was influenced by age and weight (R=0.66, R2=0.43, p<0.001) and corresponded to 90.9±4.9%PTHMAX. Moreover, PThMAX (R=0.96; R2=0.92, p<0.001) was the main determinant in the proposed equation. Additionally, we observed an inadequate ventilatory response, reduced inspiratory muscle efficiency and increased perceived effort at the end of inspiratory endurance exercise at PThC. Furthermore, the equation developed in the present study will allow to determine the PThC in a single visit, which is fundamental for the implementation of an IMT program using this load in future studies. As for the autonomic cardiovascular control, there is no consensus on the effects of IMT on the autonomic nervous system (ANS) responses. This is due to the fact that no studies were performed to evaluate the cardiovascular responses during high-intensity inspiratory endurance exercise, nor to evaluate autonomic cardiac control through non-linear methods. Therefore, our Second Study aim was to evaluate the effect of high-intensity inspiratory endurance exercise on heart rate variability (HRV) using linear and non-linear approaches. The healthy young participants of this study (n=20) performed different high-intensity inspiratory endurance exercises (80%, 95%, 100%PThMAX and PThc), which consisted in constant load tests until task failure. Moreover, the heart rate dynamics baseline (WITHOUT mouthpiece, WITH mouthpiece and SHAM) was collected in sitting position. The results of this study showed that symbolic analysis identified a more pronounced increase in sympathetic modulation (0V%) when severe exercise intensity loads were applied (95% and 100%PThMAX) (p<0.001). Increased sympathetic modulation was associated with an increase in metabolic demand (VO2) and changes in the respiratory pattern (Ti/Ttot) (p<0.001). As observed, breathing pattern has a great impact on the dynamics of autonomic cardiac control; however, the use of an inspiratory resistance load may potentiate changes in cardiovascular dynamics. Thus, the aim of our Third Study was to characterize the baroreflex sensitivity (BRS) behavior during high-intensity inspiratory endurance exercise using the sequence method (αSEQ), transfer function spectral analysis (αFT(BF)) and the closed loop model (αCL). The participants and the experimental protocol were the same reported in the Second Study. Results 3 showed that there is a decrease in BRS during high-intensity inspiratory endurance exercise when compared to rest conditions (p<0.001), and that all the methods applied in this study were efficient for BRS characterization. However, αFT(BF) was the most effective index to quantify the effects of inspiratory load on the autonomic cardiovascular control evaluated by BRS. Conclusions: the results of the present thesis showed that the concept of critical power can be applied to the inspiratory muscles to determine the PThC, which marks the transition between intense and severe inspiratory exercise. In addition, acute ventilatory, metabolic and autonomic cardiovascular control responses (HRV and BRS) observed during acute high-intensity inspiratory endurance exercise allow us to extend the PThC use to assess inspiratory muscle performance and to prescribe a high-intensity IMT program until PThC in populations like that studied in this thesis.